PENGARUH LEVERAGE, UKURAN PERUSAHAAN, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN TAX AVOIDANCE SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BEI TAHUN 2019-2023 - Romadhani, Riska Suci; Subaida, Ida; Sari, Lita Permata (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Company value is a crucial factor that companies must pay attention to in order to gain investor confidence. Company value is often associated with stock price as a benchmark for a company's success. If a company's value is high, its stock price is also likely to be high. This study aims to examine the impact of Leverage, Firm Size, and Capital Structure on Company Value through Tax Avoidance. The sampling technique used in this research is Purposive Sampling. The population in this study consists of energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the analysis hypothesis using the Smart Partial least square PLS 3.0 show that Leverage has a significant positive effect on Tax Avoidance, Firm Size has not significant effect on Tax Avoidance, and Capital Structure has not significant effect on Tax Avoidance. Leverage has not significant effect on Company Value, Firm Size has significant effect on Company Value, and Capital Structure has not significant effect on Company Value. Tax Avoidance has not significant effect on Company Value. The indirect effect hypotheses indicate that Leverage on Company Value through Tax Avoidance is not significant, Firm Size on Company Value through Tax Avoidance is not significant, and Capital Structure on Company Value through Tax Avoidance is not significant.